2011
DOI: 10.1177/0148607110374058
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin Reduces Activation of Hepatic Apoptotic Pathways and Improves Survival in Experimental Hemorrhagic Shock

Abstract: Background Hemorrhagic shock results in cellular damage and cell death. A primary mechanism is cellular apoptosis from mitochondrial damage. This study demonstrated that administration of crocetin to experimental animals during resuscitation from shock significantly improved postshock survival and reduced apoptosis. Crocetin is a component of saffron and has long been used in traditional medicine in Asia. Methods Male Sprague-Dawley rats (350 ± 30g) were randomly assigned to 1 of 4 groups of 8 animals. Hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Haemorrhagic shock and reperfusion injury have been associated with organ damage and apoptosis. Studies show that the administration of antioxidants is effective in reducing apoptosis following HS in animal models (Yang et al 2011). Other investigators have observed that production of H 2 O 2 coincided with antioxidant depletion in cells undergoing apoptosis (Takayanagi et al 1987).…”
Section: P Bennetts and Othersmentioning
confidence: 98%
“…Haemorrhagic shock and reperfusion injury have been associated with organ damage and apoptosis. Studies show that the administration of antioxidants is effective in reducing apoptosis following HS in animal models (Yang et al 2011). Other investigators have observed that production of H 2 O 2 coincided with antioxidant depletion in cells undergoing apoptosis (Takayanagi et al 1987).…”
Section: P Bennetts and Othersmentioning
confidence: 98%
“…Crocetin, the major component of saffron, is a low molecular weight carotenoid compound ( 14 ). Numerous studies have been performed to indicate the medicinal properties of crocetin, including antioxidative ( 15 ), antihypertensive ( 16 ), antithrombotic ( 17 ), anti-inflammatory ( 18 ), cardioprotective ( 19 ), hepatoprotective ( 20 ) and neuroprotective ( 21 ) effects. Crocetin also exhibits anticancer and antitumor properties.…”
Section: Introductionmentioning
confidence: 99%
“…Crocetin administration to experimental animals during resuscitation post hemorrhage increased survival, at least in part by protecting the liver from activation of apoptotic cell death [116].…”
Section: Molecular Mechanisms Involved In the Protective Effect Of Samentioning
confidence: 98%